Assessment of Vegetable Crop Productivity in Abu Al-Khasib District According to Soil Salinity Levels - Hashim Hussein Ali , Assist. Prof. Dr. Mohammad (Basra studies journal, 2026)
Soil salinity was investigated in Abu Al-Khasib District, at Basra Governorate, with the aim of identifying the spatial and temporal variability of salinity and its impact on agricultural crop productivity. The results revealed considerable variation in soil salinity levels, ranging from moderate to high in levee soils, and from high to very high in basin soils, with temporal differences observed between the two agricultural seasons and among different locations. Consequently, overall crop productivity declined, particularly in basin soils. However, the productivity of certain crops, such as cowpea and tomato, was relatively higher compared to less salt-tolerant crops like carrot and onion. The study also proposed recommendations to mitigate the adverse effects of soil salinity on agricultural production in the region.